A survey on resource sharing among libraries in Bogor area, Indonesia - Hidayat W., Sjarif (1986)
The purpose of this study is to describe the nature and prospects of resource sharing activities among agriculture-based libraries in Bogor area, Indonesia, and to identify the problems and factors that hinder or enhance resource sharing among them.